Enhancing Hotel Industry Resilience: The Role of Strategic Innovation - Haerul, Haerul; Asmar, Asmar; Salam, Rudi (Universitas Negeri Makassar, 2024)
The hotel industry in Indonesia faces an increasingly dynamic and competitive environment, particularly following the impacts of global crises such as the COVID-19 pandemic. This research explores how strategic innovation contributes to enhancing organizational resilience within the Indonesian hotel industry. The study aims to examine the role of innovation in helping hotels adapt to market volatility and sustain long-term performance. Using a qualitative approach, data were collected through in-depth interviews with key stakeholders from various hotels across Indonesia, including managers and innovation teams. The interviews focused on how strategic innovation is employed to mitigate operational disruptions, respond to shifts in customer preferences, and enhance overall resilience. The findings reveal that strategic innovation, particularly in the areas of digital transformation, service development, and operational efficiency, significantly enhances organizational resilience by enabling hotels to adapt swiftly to changing environments. Moreover, hotels that actively foster an innovation culture and integrate technology-driven solutions demonstrate greater agility and sustainability in their operations. The study concludes that strategic innovation is a vital element for building resilience in the Indonesian hotel industry, offering insights for industry practitioners to improve their adaptive capabilities and ensure long-term competitiveness. This research contributes to the growing body of knowledge on resilience in the hospitality sector, particularly in emerging markets like Indonesia, and suggests further studies to explore the quantitative impact of innovation on organizational performance.